2013
DOI: 10.1016/j.jtcvs.2013.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Six-year integrated cardiothoracic surgery residency applicants: Characteristics, expectations, and concerns

Abstract: We found that most of the candidates for 6-year integrated cardiothoracic surgery residency were young, high-achieving individuals oriented toward academic careers with a significant interest in dedicated research time and cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 13 publications
(11 reference statements)
3
28
0
Order By: Relevance
“…Interestingly, faculty slowing down to teach in the operating room was less commonly cited as a challenge (29% of residents). This is consistent with a survey of integrated resident applicants in which concern regarding the willingness of faculty to teach junior residents was cited by only 14%, whereas concerns about development of a wellrounded cardiothoracic surgeon and uncertainty in the employment and fellowship market was cited by 31% and 28% of applicants, respectively [6]. In contrast to the minority of residents in the present study (29%) who identified faculty handling residents' relative inexperience as a key challenge, the majority of program directors surveyed in 2014 perceived challenges of the integrated paradigm centered around training residents with less clinical and technical experience [5].…”
Section: Challenges Of the Integrated Paradigmsupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, faculty slowing down to teach in the operating room was less commonly cited as a challenge (29% of residents). This is consistent with a survey of integrated resident applicants in which concern regarding the willingness of faculty to teach junior residents was cited by only 14%, whereas concerns about development of a wellrounded cardiothoracic surgeon and uncertainty in the employment and fellowship market was cited by 31% and 28% of applicants, respectively [6]. In contrast to the minority of residents in the present study (29%) who identified faculty handling residents' relative inexperience as a key challenge, the majority of program directors surveyed in 2014 perceived challenges of the integrated paradigm centered around training residents with less clinical and technical experience [5].…”
Section: Challenges Of the Integrated Paradigmsupporting
confidence: 86%
“…In that study, the authors found that integrated residents spent a similar duration on adult cardiac and congenital rotations, but more time on general thoracic compared with the traditional programs, and more time on "other" rotations (cardiac catheterization, echocardiography, etc) [4]. Variability in curriculum structure has been discussed as a concern for integrated programs [5,6], although this variability in curriculum has not been specifically assessed. Studies are also lacking as to the relevance of these rotations to the ultimate success of residents or obtainment of particular skills.…”
Section: Commentmentioning
confidence: 99%
“…In a recent survey of I-6 program applicants, Tchantchaleishvili and colleagues 1 reported that most candidates were young, high-achieving individuals oriented toward academic careers; however, the sample size was small (36 respondents, 45% response rate). Ward and colleagues 2 compared the curricula between I-6 and traditional training programs.…”
mentioning
confidence: 99%
“…Strategies have been developed in thoracic surgery and in surgical education as a whole to incorporate more simulation, more structured curricula, and clear outlines for achieving educational goals in a particularly challenging environment [1,5,6]. New training paradigms have been developed, and faculty programs to "educate the educators" have gained momentum [7][8][9].…”
mentioning
confidence: 99%